Ethical assessment of privacy breaches in epidemiological investigations and information disclosure in the internet age: Safeguarding identity information for infectious patients - Zhang, Zhen; Zang, Zheng (Acta Bioethica, 2024)
While the Internet has brought convenience and speed to human life, it has also led to frequent privacy violations. In the context of epidemiological investigations and information disclosure regarding confirmed Covid-19 patients, many individuals have utilized the Internet as a means to disseminate information and engage in cyber manhunts, resulting in breaches of privacy for those involved. This phenomenon is particularly prevalent within the realm of the Internet, where the boundaries of privacy invasion become blurred. Various types of privacy infringements, both active and passive negligence, are evident on social networking platforms. The juxtaposition of the virtual world of the Internet with real-life scenarios presents novel challenges in the realm of privacy violations. The Internet era, coupled with the widespread use and integration of big data, has diminished the absolute right to privacy on the Internet. This paper examines the challenge of safeguarding the identity information of infectious patients through the lens of two theoretical frameworks —Kantianism and Utilitarianism— in an effort to address this ethical dilemma.